TOXIC METALS LEVELS IN AGROCHEMICALS SOLD IN SABON GARI MARKET, KANO, NORTHWESTERN NIGERIA - Abdullahi, Ibrahim Lawal; Sani, Ali; Yusuf, Yusuf Adam (FUDMA JOURNAL OF SCIENCES, 2023)
Heavy metals such as Cadmium (Cd), Nickel (Ni), lead (Pb), Zinc (Zn), and Copper (Cu) originate from various sources including agriculture. From agricultural sources, they comprise agrochemicals such as insecticides and pesticides. The study aimed at evaluating the levels of toxic metals in agrochemicals (pesticides) sold at Sabon Gari market, Kano. 42 brands of pesticides were obtained from the market. They were digested and then analyzed by Atomic Absorption Spectrophotometer for determination of Cd, Pb and Ni. Cd was found to be highest in LF (0.0833mg/l) and least in RCK (0.0015mg/l) while not detected in CBT, CPT, DDF, and PRF. Pb was found to be highest in FUP (2.995mg/l) and least in PRF (0.0434mg/l) while not detected in BF, CLV, CPF, CPT, DDF, GRF, LCH, LF, PK, and RV. Ni was only detected in DDF (0.305mg/l). Therefore, it is clear that the pesticides contain heavy metals slightly above the tolerable limits which could get into the soil subsequently accumulate overtime and pose serious threat to the plants and other living organisms.
Keywords: Agrochemicals; Heavy metals; Insecticides; Monitoring; Pesticides